Dog sledders ("Mushers"), five men in arctic dress, ca. 1910 - Thwaites, John E. (John Edward), 1863-1940 (1910)
Caption on image: Mushers, Alaska PH Coll 247.343 Someone who drives, or "mushes", a dog team is known as a musher. The word probably comes from the French word "marcher", which means "to walk".